Utility of Chitra-HASi granules in cystic defects of the maxillofacial region: A pilot study - Manikandhan Ramanathan; Raj Kumar Tiwari; Sunil Paramel Mohan; Dayasankar Prabhu Shankar; Ritvi K Bagadia; P R Harikrishna Varma; Francis Boniface Fernandez; S Suresh Babu (Wolters Kluwer Medknow Publications, 2021)
Background: Cystic defects that are critical sized or larger require bone replacement strategies. However, due to inherent disadvantages of the various types of grafts, none of the available materials are best suited for these defects. Among the alloplastic materials, hydroxyapatite (HA)-based grafts are the most popular, due to their osteoconductive nature and resemblance to mineral bone. The aim of the study was to assess the utility of the novel material "Chitra-HASi" as a bone substitute in the maxillofacial region. Materials and Methods: In a single-arm, prospective study, patients with radicular and dentigerous cysts were included and the minimum defect size was standardized at 20 × 20 mm or above. The Chitra-HASi material was developed by a wet precipitation technique and adopted for use following multiple in vitro and in vivo studies, confirming its safety and biocompatibility profile. All cysts underwent enucleation, followed by peripheral ostectomy and apicectomy of the teeth involved. The HASi graft was packed inside the cystic defect in a granular form and covered with a mucoperiosteal flap. Panoramic radiographs were taken preoperatively and at 3, 6, and 12 months postoperatively. Results: Twenty-three patients were included in the study, of which only 10 patients could be followed up for 12 months after graft placement. The mean preoperative bone density was found to be 14.9% ± 4.97 (standard deviation), whereas the postoperative 3-month, 6-month, and 12-month densities had a mean difference of −11.3%, −22.9%, and −37.3%, respectively, and the differences were statistically significant. Minor complications such as sinus formation (n = 7) and extrusion of granules (n = 4) were noted, which were managed conservatively. Only two patients required graft removal secondary to infection, leading to a persistent sinus tract. Conclusion: The results of the study suggest that Chitra-HASi granules show potential as an alternative to other bone substitutes. The addition of silica to the porous HA material offers superior strength characteristics and needs long-term evaluation to assess its stability in large cystic defects.